Neutrophils exacerbate tuberculosis infection in genetically susceptible mice. Issue 4 (July 2015) - Yeremeev, Vladimir; Linge, Irina; Kondratieva, Tatiana; Apt, Alexander
Summary Mice of the I/St inbred strain genetically hyper-susceptible to TB infection and prone to form neutrophil-abundant necrotic lung lesions and relatively resistant mice of the C57BL/6 (B6) strain were infected with 100 CFU of M. tuberculosis H37Rv. To verify the role of neutrophils in TB immunity, we selectively depleted neutrophils from infected mice with highly specific 1A8 anti-Ly6G antibodies at day 2 and 6 post-challenge. Depletion of neutrophils resulted in reduced lung tissue pathology, mycobacterial CFU counts and an increase of the survival time in genetically susceptible I/St, but not in B6 mice. Furthermore, we demonstrated that in vivo neutrophil depletion at the onset of TB infection results in a significant increase in numbers of mycobacteria-specific IFN-γ-producing T-cells at the time point when the acquired immunity to mycobacteria is fully developed. These results suggest antagonistic activity of neutrophils and immune T-cells in the course of TB infection and provide further evidence of deleterious rather than protective role of the former.